Correlation between transverse cerebellar diameter and gestational age in second and third trimester of singleton pregnancies - Beenish Nadeem; Anam Zahoor (Journal of University Medical & Dental College, 2022)
BACKGROUND & OBJECTIVE: Trans cerebellar diameter stands out as an important fetal parameter for estimating gestational age in second and third trimester when all the other parameters start showing margin of error of 3 to 4weeks. The study was designed with intent to gather more evidence on TCD measurements validity.  This will help us in using TCD on routine basis in advance pregnancies. Our objective is to determine the correlation between mean transverse cerebellar diameter and mean gestational age in 20 to 40 weeks of gestation.METHODOLOGY: This research is being conducted at radiology department of Social Security Hospital Islamabad from 1-02-2022 till 01-06-2022. Non-probability convenient sampling was done and a total of sixty (n=60) healthy women with a singleton pregnancy between 18 to 40 years of age with gestational age of 20 to 40 weeks as confirmed by ultrasound were enrolled in the study. An expert radiologist used Logic P6 ultrasonography machine during the study. TCD, HC, BPD and FL was measured in each patient and correlated with gestational age. Pearson correlation coefficient was computed using SPSS-17.0.RESULTS: Significant and strong positive correlation (r=0.98) and p<0.001 was found between TCD measured by ultrasonography and gestational age at a 0.05 significance level.CONCLUSION: Significant and strong positive correlation was found between TCD measured by ultrasonography and gestational age.